Effects of Emerging Alcohol and Marijuana Use Behaviors on Adolescents’ Neuropsychological Functioning Over Four Years - Nguyen-Louie, Tam T. (J Stud Alcohol Drugs, 2015)
OBJECTIVE: Adolescence is a period of neuromaturation concomitant with increased substance involvement. Most substance use studies of adolescents have focused on categorical classifications (e.g., dependent vs. nondependent), but little is known about the influence of specific substance use behaviors on cognitive functioning in youth. METHOD: This study prospectively evaluated the quantitative effects of different substance use behaviors on neuropsychological functioning. A cognitive test battery was administered at baseline (ages 12–14 years), before substance use initiation, and at follow-up (M = 4.0 years, SD = 2.0) to evaluate changes in verbal memory, visuospatial ability, psychomotor speed, processing speed, and working memory. Robust regressions examined substance use behaviors as predictors of neuropsychological functioning (N = 234). RESULTS: Several substance use behaviors predicted follow-up neuropsychological functioning above and beyond effects of baseline performance on the same measure (ps < .05). Specifically, more alcohol use days predicted worse verbal memory ([Image: see text] = -.15) and visuospatial ability ([Image: see text] = -.19). More postdrinking effects ([Image: see text] = -.15) and greater drug use ([Image: see text] = -.11) predicted worse psychomotor speed. Processing speed was not predicted by substance involvement (ps > .05). Unexpectedly, more alcohol use predicted better working memory performance ([Image: see text] = .12). CONCLUSIONS: The frequency and intensity of adolescent alcohol use may be more intricately linked to neuropsychological outcomes than previously considered. The low prevalence of substance use disorder in the sample suggests that subdiagnostic users may still experience adverse effects to verbal memory, visuospatial functioning, and psychomotor speed after initiating intense or frequent alcohol use.